Evaluating TPACK Knowledge and Skills Among Arabic Pre-Service Teachers in Implementing Online Assessment During Movement Restriction Control (MCO) Of COVID-19 - Sahrir, Muhammad Sabri; Zaini, Abdul Razif; Hamid, Mohd Azrul Azlen Abd.; Hamat, Zulkefli; Ismail, Taufik (The journal of contemporary issues in business and government, 2021)
The importance of having the knowledge and skills in Technological Pedagogical Content Knowledge (TPACK) among teachers when dealing with teaching via technology is very clear. In TPACK, there are three essential components that need to be practiced during teaching and learning in using technologies, including the current situation of COVID-19 pandemic. This study was conducted to evaluate the level of TPACK knowledge and skill among Arabic trainee teachers in implementing online teaching and assessment during Movement Restriction Control (MCO) of COVID-19 by the Malaysian government, whereby the schools are closed to face-to-face learning activities. The pre-service teachers were purposively selected among final year students of Bachelor of Education in Teaching Arabic as a Second Language, from the Kulliyah of Education, International Islamic University Malaysia (IIUM). They weresentto various secondary schools in Selangor to complete the graduation requirement of Bachelor of Education degree in teaching practicum. The research instruments were investigating the teachers’ knowledge about three essential components of TPACK, which include technology, content, and pedagogy as well as open-ended surveys on obstacles and challenges in home-based teaching and online assessment of Arabic language before and during MCO, online learning platforms used and further suggestions to improve the use of technology in implementing online assessment of Arabic language teaching in schools during pandemic. Thefindings showed that the understanding of the trainee teachers’ level of knowledge and understanding of TPACK is very good towards implementing online teaching and assessment during the home-based and online teaching during pandemic. The responses of online learning platforms used and proposed suggestions to improve the use of technology in implementing online assessment may also beneficial to teachers in preparing the online teaching and assessment in home-based setting during COVID-19 pandemic.